Cloud-based Middleware for Syntactical Interoperability in Internet of Things - Pramukantoro, Eko Sakti; Bakhtiar, Fariz Andri (Faculty of Computer Science (FILKOM) Brawijaya University, 2020)
Heterogeneity of protocol communications, data formats, data structure, and hardware specifications on the Internet of things can lead to an Interoperability problem. The solution provides middleware that capable to work in heterogeneity communications, data formats, etc. This paper proposed. A cloud-based middleware that provides a communication interface to receive data from sensor nodes based on Restful and CoAP. Received data then stored in heterogenous IoT data storage based on the NoSQL database. From experiment and testing, interoperability testing methodology was used. The result shows proposed middleware can receive data from both protocols. The received data could store based on structure data or unstructured data on IoT data storage.